Network pharmacology and molecular docking investigation of Curcuma xanthorrhiza Roxb. rhizome with the mechanisms underlying as the potential drug of eczema treatment - Pratama, Yusuf Alif; Dzikri Marhaeny, Honey; Winarto, Sulistyanengci; Palmado, Igansius Agyo; Hermawan, Muhammad; Widyananda, Widyananda; Rahmadi, Mahardian; Bakhtiar, M. Taher; Hasan, Ahmed Abdallah; Kleuser, Burkhard; Khotib, Junaidi (Wolters Kluwer Medknow Publications, 2025)
A chronic inflammatory dermatosis, eczema, affects more than 12% of the pediatric population and 7.2% of adults. Clinically, it presents with erythematous, scaly, and intensely pruritic lesions. Severe forms of the disease frequently exhibit poor responsiveness to treatments aimed at a single inflammatory pathway. Curcuma xanthorrhiza Roxb. rhizomes possess antioxidant, anti-inflammatory, and anti-allergic activities through a multi-target mechanism. This study aimed to evaluate the secondary metabolites of C. xanthorrhiza Roxb. rhizomes that can be developed into eczema drugs using virtual screening in silico. Secondary metabolite compounds from C. xanthorrhiza rhizomes were evaluated for their drug-likeness properties Subsequently, the similarity of their physicochemical properties was assessed using the principal component analysis. A target search of drug candidates was performed using the Swiss Target Prediction and Gene Expression Omnibus (GEO) Omnibus. Docking was performed using Molegro by comparing the rerank scores of the drug candidates with those of the original ligands. Absorption, distribution, metabolism, excretion, and toxicity (ADMET) prediction was performed using the pkCSM. Carbonic anhydrase II, epidermal growth factor receptor, and the mammalian target of rapamycin came as the protein target for eczema disease. For the docking result, demethoxycurcumin (C00037023), 1,5-dihydroxy-1,7-bis (4-hydroxy-3-methoxyphenyl)-4,6-heptadien-3-one (C00055412), 1,7-bis (4-hydroxy-3-methoxyphenyl)-3,5-heptanediol (C00055175), and 3’-demethoxycyclocurcumin (C00054761) had both better rerank score than the native ligand and good ADMET profiles. Four compounds derived from C. xanthorrhiza Roxb. rhizomes can be developed as an eczema potential treatment